SISTEM PENGUKURAN SUHU TUBUH OTOMATIS BERBASIS ARDUINO SEBAGAI ALAT DETEKSI AWAL COVID-19 - Iqbal Ardiyansah; Lela Nurpulaela (Politeknik Harapan Bersama Tegal, 2021)
Public places such as offices, factories or public facilities are places that have high risk of COVID-19 transmission. Therefore, proper and fast precautions are needed, by complying with health protocols, including that every employee or person who wants to enter an office building, factory or other public facilitiesis checked for temperature by officers as early detection of COVID-19. This study discusses the design of an Arduino-based automatic body temperature measuring device which has a reminder alarm if the body temperature is above 37.30 °C. This tool is connected to a smartphone or computer device via bluetooth. This body temperature measuring device utilizes the DS18B20 sensor to measure temperature in units of Celsius (0C). The data is also displayed in the 16x2 (cm) LCD on it. The results of the test for measuring body temperature is compared to thermo gun, have a deviation range of 1,05-1,92%. It is expected that this body temperature measuring device can be installed in public places that need to carry out checks on people who want to enter the buildings or offices. Fortunetly, the operators can stand in the saving place that is far away from the virus trnsmission.